Juridical Review Concerning Civil Liability of Mutual Fund Investment Managers Against Lossed Investors - Raden Ati Haryati; Enggar Widianingrum; Nyoman Suardhita; Agus Suhaila (LEGAL BRIEF, 2022)
Investment Manager is the party that manages the securities portfolio for customers or manages the collective investment portfolio for a group of customers based on the prevailing laws and regulations. One of the Mutual Fund products is the Equity Fund. The Investment Manager in managing Equity Mutual Funds carries out portfolio activities, both securities portfolios and collective investment portfolios. Portfolios are intended to minimize the risks that occur when managing investments. With the existence of a portfolio, it is hoped that the rate of return expected by investors can be achieved optimally. In managing a Equity Mutual Fund, mistakes are never made. Investment Manager errors can cause losses on the part of investors. As for the problem, what are the actions of the Investment Manager in carrying out stock portfolio activities that can harm investors in equity mutual funds, what is the civil liability of the Investment Manager to investors who are harmed in the Equity Mutual Fund, and where investors can file a complaint against the actions of the Investment Manager. to the detriment of investors. The research method carried out by the author is library research, namely the activity of collecting data and provisions in laws and regulations that have binding legal force, both regulations issued by the government of the Republic of Indonesia and regulations issued by BAPEPAM-LK. In addition, data is also collected from books and internet media. Based on the research conducted by the author, it can be concluded that: Investment Manager's actions in carrying out stock portfolio activities that can harm investors in Equity Mutual Funds include actions that are prohibited for Investment Managers as regulated in Article 35, Article 41, and Article 42 of the Law No. 8 of 1995 concerning the Capital Market. If the Investment Manager is proven to have committed an act that can cause harm to the investor, the Investment Manager is responsible for compensating the loss, and if the Investment Manager does not want to compensate for the loss, the investor can file a complaint with BAPEPAM-LK or file a lawsuit with the District Court. It is hoped that before investors invest in an Mutual Fund, the investor should know in advance the vision and mission of the Investment Manager who manages the Mutual Fund, including the soul, spirit, and also the characteristics of the Investment Manager Representative who is appointed as the person in charge of carrying out operational management activities. The Mutual Funds, including the preparation of the Securities portfolio which is the basis for the existence of the Mutual Funds.